Computed tomographic findings in subjects who died from respiratory disease in the National Lung Screening Trial. Issue 4 (20th April 2017) - Pompe, Esther; de Jong, Pim A.; Lynch, David A.; Lessmann, Nikolas; Išgum, Ivana; van Ginneken, Bram; Lammers, Jan-Willem J.; Mohamed Hoesein, Firdaus A.A.
We evaluated the prevalence of significant lung abnormalities on computed tomography (CT) in patients who died from a respiratory illness other than lung cancer in the National Lung Screening Trial (NLST). In this retrospective case–control study, NLST participants in the CT arm who died of respiratory illness other than lung cancer were matched for age, sex, pack-years and smoking status to a surviving control. A chest radiologist and a radiology resident blinded to the outcome independently scored baseline CT scans visually and qualitatively for the presence of emphysema, airway wall thickening and fibrotic lung disease. The prevalence of CT abnormalities was compared between cases and controls by using chi-squared tests. In total, 167 participants died from a respiratory cause other than lung cancer. The prevalence of severe emphysema, airway wall thickening and fibrotic lung disease were 28.7% versus 4.8%, 26.9% versus 13.2% and 18.6% versus 0.5% in cases and controls, respectively. Radiological findings were significantly more prevalent in deaths compared with controls (all p<0.001). CT-diagnosed severe emphysema, airway wall thickening and fibrosis were much more common in NLST participants who died from respiratory disease, and CT may provide an additional means of identifying these diseases. Pulmonary abnormalities on CT are common in lung cancer screening and identification may add to the yield of screening http://ow.ly/qFUu308zbnC